Jews and protestants : from the Reformation to the present - Aue-Ben-David, Irene; Elyada, Aya; Sluḥovsḳi, Mosheh; Wiese, Christian (2020)
The volume sheds light on various chapters in the long and multifaceted history of Protestant-Jewish relations, from the Reformation to the present. Going beyond theological questions to the areas of philosophy, music, sociology, and language, it showcases current trends in present-day scholarship and opens up directions for research on this intricate topic, which bears both historical significance and evident relevance to our own time.